Analisis Guarantee Floating Deposit Terhadap Mitigasi Piutang Tak Tertagih Di Industri Perhotelan - Anak Agung Ayu Linawati (Hita Akuntansi dan Keuangan, 2026)
Uncollectible receivables are a common issue faced by the hospitality industry and can affect the financial stability of hotels. To minimize the risk of bad debts, hotels often implement specific financial control policies, one of which is the Guarantee Floating Deposit (GFD). However, the effectiveness of this policy is not solely determined by established systems and procedures but is also influenced by human resource factors, including employee motivation, work environment, and employee performance. This study aims to analyze the implementation of the Guarantee Floating Deposit policy in controlling uncollectible receivables at Hotel PSB using a qualitative research approach. Data was collected through in-depth interviews, observations, and documentation. The research informants consisted of management and employees directly involved in sales activities, receivables collection, and accounts receivable management within the hotel. The findings reveal that the implementation of the Guarantee Floating Deposit policy plays a significant role in reducing the risk of uncollectible receivables. Furthermore, strong work motivation and a supportive work environment contribute to improved employee performance in consistently and responsibly implementing the Guarantee Floating Deposit policy. Optimal employee performance is reflected in adherence to procedures, timeliness and accuracy in receivables collection, and effective coordination among departments. Therefore, the control of uncollectible receivables at Hotel PSB requires not only appropriate financial policies but also effective human resource management